PROPERTIES OF CLASSICAL Be STARS FROM ANALYSIS OF HIGH-RESOLUTION H PROFILES - Miroshnichenko, A. S.; Bjorkman, K. S.; Krugov, V. D.; Usenko, I. A. (Одеські астрономічні публікації, 2017)
We summarize results of the 25 year period of observations of Be-stars. We suggest that Be stars with moderate and strong Hα emission are good candidates to search for binary systems.